2021
DOI: 10.1093/synbio/ysab031
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas9 method facilitates efficient oligo-mediated gene editing in Debaryomyces hansenii

Abstract: The halophilic and osmotolerant yeast Debaryomyces hansenii has a high potential for cell factory applications due to its resistance to harsh environmental factors and compatibility with a wide substrate range. However, currently available genetic techniques does not allow the full potential of D. hansenii as a cell factory to be harnessed. Moreover, most of the currently available tools rely on the use of auxotrophic markers that are not suitable in wild-type prototrophic strains. In addition, the preferred n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…First, we set out to identify a working transformation protocol and a functional selectable marker gene for C. intermedia . Like many other CTG clade yeast (Vyas et al 2015 , Norton et al 2017 , Ennis et al 2021 , Strucko et al 2021 ), C. intermedia displayed sensitivity to cloNAT in the concentration of 10–1000 µg/ml (data not shown), of which 200 µg/ml was chosen in further experiments. We transformed C. intermedia using electroporation and a linearized CaNAT1 marker cassette that has proven effective in numerous yeast including C. albicans, C. parapsilosis , and C. intermedia ’s close relative Clavispora lusitaniae (outlined in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…First, we set out to identify a working transformation protocol and a functional selectable marker gene for C. intermedia . Like many other CTG clade yeast (Vyas et al 2015 , Norton et al 2017 , Ennis et al 2021 , Strucko et al 2021 ), C. intermedia displayed sensitivity to cloNAT in the concentration of 10–1000 µg/ml (data not shown), of which 200 µg/ml was chosen in further experiments. We transformed C. intermedia using electroporation and a linearized CaNAT1 marker cassette that has proven effective in numerous yeast including C. albicans, C. parapsilosis , and C. intermedia ’s close relative Clavispora lusitaniae (outlined in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Our analysis showed that C. intermedia is a haploid yeast belonging to the CTG clade of ascomycetous yeast, where the universal CUG codon is predominantly translated into a serine rather than a leucine (Geijer et al 2020 , Muhlhausen et al 2021 ). The CTG clade comprises many relatively well-studied yeasts including human pathogens Candida albicans, Candida tropicalis, Candida parapsilosis , and industrially attractive yeasts such as Debaryomyces hansenii, Metschnikowia pulcherrima , and Scheffersomyces stipitis (Enkler et al 2016 , Cao et al 2018 , Muhlhausen et al 2021 , Strucko et al 2021 , Zhang et al 2022 ). Genome editing tools have been developed for many of these species, which means that several CTG clade-compatible plasmids containing selectable marker genes and reporter systems are available (Papon et al 2012 , Lobs et al 2017 , Uthayakumar et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…YFP has been chosen in this work and has been cloned into the yeast by random integration. Although CRISPR/Cas9 tools to genetically modify D. hansenii are now available (Strucko et al, 2021 ), it is still unknown which integration sites in the genome of this yeast are the most suitable to introduce a recombinant gene for optimal expression. Hence, random integration has been chosen as an alternative in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The transformation was performed following the electroporation protocol described by Strucko et al ( 2021 ), using the MicroPulser electroporator (BioRad) on manual settings at 2.3 kV. YPD + NTC agar plates were used for the selection of the transformant cells.…”
Section: Methodsmentioning
confidence: 99%